Route to 1, 2, 4- and 1, 2, 5-oxadiazole ring assemblies via a one-pot condensation/oxidation protocol. Issue 13 (26th March 2020) - Teslenko, Fedor E.; Churakov, Artem I.; Larin, Alexander A.; Ananyev, Ivan V.; Fershtat, Leonid L.; Makhova, Nina N.
Graphical abstract: Highlights: A new method for the synthesis of (1, 2, 4-oxadiazolyl)-1, 2, 5-oxadiazoles was developed. The process involves a one-pot condensation/oxidation sequence. Previously unknown rearrangement in a furoxan series was found. Abstract: A novel one-pot approach for the synthesis of 1, 2, 4- and 1, 2, 5-oxadiazole ring assemblies has been developed. The synthetic strategy involves the condensation of furoxanyl amidoximes with aldehydes and subsequent iodine-mediated oxidation of the intermediate 1, 2, 4-oxadiazolines. The analogous reaction of 4-aminofuroxanyl-3-carboxamidoxime results not only in formation of the 1, 2, 4-oxadiazole subunit, but also rearrangement of the furoxan ring to the furazan one, which is the first example of a Lewis acid-promoted rearrangement in a furoxan series.